Enhanced Thrombin Regulation during Warfarin Therapy in Children Compared to Adults - Massicotte, Patricia; Leaker, Michael; Marzinotto, Velma; Adams, Margaret; Freedom, Robert; Williams, William; Vegh, Patsy; Berry, Leslie; Shah, Bianca; Andrew, Maureen (Thrombosis and Haemostasis, 1998)
The intensity of warfarin therapy for prevention of primary and secondary thromboembolic complications in paediatric patients, is extrapolated from guidelines for adults, which may not be optimal. Therefore, we assessed thrombin regulation ex vivo and in vitro in plasmas from 40 children (1 to 18 years old with a median age of 13 years) and 27 adults receiving warfarin with an international normalized ratio of 2 to 3 (child: 2.5 ± 0.15; adult: 2.4 ± 0.14). Ex vivo concentrations of prothrombin fragment 1.2 were significantly lower in children (0.30 ± 0.03 nM) compared to adults (0.45 ± 0.04 nM; p <0.01). Thrombin generation in defibrinated plasmas (Arvin) was decreased and delayed for children compared to adults when activated by either activated partial thromboplastin time (child = 32 ± 1.7, adult = 45 ± 1.9 μM · s) or prothrombin time (child = 35 ± 0.7, adult = 46 ± 1.0 μM · s) reagents (p <0.01 for both). Although plasma concentrations of factors (F) II, FVII, FIX, F X, protein C and protein S were similar, more of the thrombin generated was complexed to α2 macroglobulin (α2M) at times close to peak thrombin activity (60 s) in plasma from children (general linear analysis of variance; p <0.03). Thus, increased α2M levels may enhance thrombin regulation in paediatric compared to adult patients receiving warfarin, suggesting that clinical trials in children, using less intense warfarin treatment, may be required to determine optimum therapy.